FGF21: A Novel Regulator of Glucose and Lipid Metabolism and Whole-Body Energy Balance - Szczepańska, Ewa; Gietka-Czernel, Małgorzata (Hormone and Metabolic Research, 2022)
Fibroblast growth factor (FGF) 21 is a recently recognized metabolic regulator that evokes interest due to its beneficial action of maintaining whole-body energy balance and protecting the liver from excessive triglyceride production and storage. Together with FGF19 and FGF23, FGF21 belongs to the FGF family with hormone-like activity. Serum FGF21 is generated primarily in the liver under nutritional stress stimuli like prolonged fasting or the lipotoxic diet, but also during increased mitochondrial and endoplasmic reticulum stress. FGF21 exerts its endocrine action in the central nervous system and adipose tissue. Acting in the ventromedial hypothalamus, FGF21 diminishes simple sugar intake. In adipose tissue, FGF21 promotes glucose utilization and increases energy expenditure by enhancing adipose tissue insulin sensitivity and brown adipose tissue thermogenesis. Therefore, FGF21 favors glucose consumption for heat production instead of energy storage. Furthermore, FGF21 specifically acts in the liver, where it protects hepatocytes from metabolic stress caused by lipid overload. FGF21 stimulates hepatic fatty acid oxidation and reduces lipid flux into the liver by increasing peripheral lipoprotein catabolism and reducing adipocyte lipolysis. Paradoxically, and despite its beneficial action, FGF21 is elevated in insulin resistance states, that is, fatty liver, obesity, and type 2 diabetes.
Keywords: FGF21; insulin sensitivity; appetite; blood glucose; triglycerides; NAFLD